WOUND HEALING POTENTIAL OF ZINGIBER OFFICINALE ESSENTIAL OIL - SURYATI SYAFRI; SENTI DWI SURYANI; IRWANDI JASWIR; FARIDAH YUSOF; DACHRIYANUS HAMIDI (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The purpose of this study was to evaluate in vitro wound healing activity through antioxidant, antibacterial, and fibroblast cell proliferation and migration capabilities of Zingiber officinale essential oil (ZEO), as well as to identify its metabolite profile. Methods: Extraction of essential oil using the hydrodistillation method. Metabolite profile was analyzed using the gas chromatography-mass spectrometry (GC-MS) technique. In vitro wound healing activity was evaluated through fibroblast cell proliferation and the fibroblast cell migration using the scratch assay. The antibacterial activity was assessed using the microdilution method against six wound-infecting bacteria, while the ABTS method measured antioxidant activity. Results: The GC-MS analysis showed citral (15.1%), camphene (14.9%), Z-citral (10.8%), and 1,8-cineole (8.0%) as major compounds. ZEO showed low antioxidant activity (IC50 >250 μg/mL). The antibacterial activity results showed the lowest minimum inhibitory concentration value and minimum bactericidal concentration value against methicillin-resistant Staphylococcus aureus at 16 μg/mL. ZEO increased fibroblast cell proliferation to 120% of the control value at a concentration of 1 μg/mL and improved wound closure by 80.52% after 48 h of incubation time at a concentration of 0.1 μg/mL. ZEO has the potential to be utilized as an alternative natural source for wound healing due to its antibacterial effects and ability to stimulate fibroblast cell proliferation and migration.